Effectiveness of Shareholders’ Collaorative Engegement Activities with Companies on CSR Issues - Valeria Piera, Piani (2009)
The main scope of this research was to identify key factors which ensure better effectiveness of investors’ collaborative engagement activities with companies on CSR issues. Theoretical propositions were developed using agency theory, stakeholder theory, institutional theory, collective action models and existing industry theory on engagement practices. Consequently, three case studies were selected from the Principles of Responsible Investment Initiative’s Clearinghouse platform following literal and theoretical replication. Using qualitative research methods, the investigation focused on the process of collaborative engagement as perceived by the investors who participated in the initiatives. Focusing both on the collaboration amongst investors and the dialogue between investors and companies. The case studies showed typical problems and barriers of collective actions as predicted in existing literature, and solutions to foster better cooperation amongst the participants were provided. Predictions on increased level of power, legitimacy and urgency through collaboration were confirmed by data. However, the insights from the analysis on the use of these attributes during the dialogue with the companies did not mirror the models proposed by the theory. According to the investors, shareholders’ salience by companies’ managers is not measured by the exercise of power, legitimacy and urgency at the same time. Conversely, investors have a tendency towards an escalation process during the collaborative engagement, giving priority to legitimacy and persistence, and using other elements of power and urgency at later stages if the first response by the companies is not satisfactory. Additionally, data did not strongly support the role of managers’ values in prompting corporate change. Even if some investors acknowledged the importance of the motivation and drive of key managers in some companies, managers’ discretion and position were the first parameters to be considered when selecting who to be in contact with during an engagement.